Design of Task Evaluation Procedures Using Analytic Hierarchy Process (AHP) Method - Rostislav Tomeš (Current Topics on Business, Economics and Finance Vol. 1, 2023)
Decision making is a crucial component of the work that teachers do in evaluating their students. To eliminate subjective effects, the teacher can employ the hierarchical decision-making process. The presented chapter describes the decision-making method, the Analytic Hierarchy Process (AHP), constructing the matrix of pair-wise comparison and calculation of the eigenvector of the pair-wise matrix using well know Microsoft Excel utilities. On the basis of short examples pertaining to the consistency of the pair-wise matrix, the AHP method’s steps are outlined. These assignment grading procedures can be used by the teacher as a helpful tool for evaluating student work.